Hermeneutic circle in digital literation and its relevance as an antidote to hoax - M. Rodinal Khair Khasri (Universitas Negeri Yogyakarta, 2019)
This article presents the results of the observations about digital literacy that were studied philosophically through Gadamer's hermeneutic approach. The reason for using this approach is to achieve an understanding of how the subject and its history play a role in the digital literacy process, where ontologically, the content of information has been visualized into the digital world so that a philosophical understanding is needed in understanding the virtual reality. This research is included in the classification of qualitative research with an analysis with three stages, namely reducing data that is very general and broad in a more specific form, and relevant to digital literacy and hermeneutics; then classifies the dimensions of digital literacy so that it is easy to determine the dimensions of the hermeneutics; interpret digital literacy to clarify the dimensions of hermeneutics in it, and concludes and draws relevance to efforts to overcome hoaxes. The results obtained from this study are on a hermeneutical analysis of the process of digital literacy as a catalyst for peace, that equalizing the elimination of discrimination at the historical-ego level can be achieved through the application of hermeneutical digital literacy that is by promoting dialectical historical understanding, where contemporary history dialecticism with the history of the past which is often claimed by certain groups as the heyday and the fruit of their work.Artikel ini mempresentasikan tentang hasil observasi peneliti tentang literasi digital yang dikaji secara filosofis melalui pendekatan hermeneutika Gadamer. Adapun alasan penggunaan pendekatan tersebut yakni untuk mencapai sebuah pemahaman tentang bagaimana subjek dan kesejarahannya berperan di dalam proses literasi digital, di mana secara ontologis, konten informasi telah divisualisasikan ke dalam dunia digital sehingga dibutuhkan pemahaman yang filosofis di dalam memahami realitas virtual tersebut. Penelitian ini masuk ke dalam klasifikasi penelitian kualitatif dengan analisis dengan tiga tahap yaitu mereduksi data yang bersifat sangat umum dan luas ke dalam bentuk yang lebih spesifik, dan relevan dengan literasi digital dan hermeneutika; selanjutnya mengklasifikasikan dimensi literasi digital sehingga mudah untuk ditentukan dimensi hermeneutikanya; menginterpretasikan literasi digital dalam rangka memperjelas dimensi hermeneutika di dalamnya; serta menyimpulkan dan menarik relevansinya dengan upaya menanggulangi hoax. Hasil yang didapatkan dari penelitian ini adalah pada sebuah analisis hermeneutis tentang proses literasi digital sebagai katalis perdamaian, bahwa penyetaraan penghapusan diskriminasi pada tataran ego-historis dapat dicapai melalui penerapan literasi digital yang bersifat hermeneutis yakni dengan mengedepankan pemahaman kesejarahan yang dialektis, di mana sejarah masa kini didialektikakan dengan sejarah masa lampau yang seringkali diklaim oleh kelompok-kelompok tertentu sebagai masa kejayaan dan buah kerja mereka.